Analisis Kendala Implementasi SIPD dalam Pengelolaan Keuangan Daerah (Studi Kasus pada BPPKAD Kabupaten Sampang) - Ach Roihan; Moh Syifauddin (Indo Publishing, 2026)
Improving the effectiveness, transparency, and accountability of regional financial management has become one of the primary objectives of digital transformation in public administration. One form of implementing this digital transformation is the adoption of the Regional Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD), developed by the Ministry of Home Affairs of the Republic of Indonesia. SIPD functions as an integrated system for regional development planning, budgeting, financial administration, reporting, and financial accountability processes. This study aims to analyze the constraints in the implementation of SIPD in regional financial management at the Regional Revenue, Financial Management, and Asset Agency (BPPKAD) of Sampang Regency. The study employed a qualitative descriptive approach using data collection techniques in the form of literature review, observation, documentation, and analysis of recent studies related to SIPD implementation in Indonesia. The findings indicate that the implementation of SIPD at BPPKAD Sampang Regency has not yet been fully optimized due to several challenges, including limited information technology infrastructure, unstable internet connectivity, SIPD server disruptions, inadequate human resource competencies, and insufficient technical training. Based on the findings, improving the quality of human resources through continuous training and assistance programs is necessary to enable local government officials to adapt to system updates and regulatory changes within SIPD. In addition, strengthening regional digital infrastructure, particularly through stable internet connectivity and adequate supporting facilities, is essential to ensure smooth system operations. Furthermore, optimizing technical support from the central government and conducting periodic system evaluations are required to identify and address implementation challenges, thereby enabling SIPD to operate more effectively, efficiently, transparently, and accountably in regional financial management.